In Silico Molecular Docking of Indigofera tinctoria Phytocompounds to Target EGFR/ERK and FGFR/FGF Pathway Proteins Involved in Prostate Cancer - Nidhi Premanand Honavar (International Journal of Molecular Biotechnological Research, 2023)
Objective: Prostate cancer being the second major cause of cancer-related deaths in males, affects the small walnut-shaped gland below the bladder called the prostate gland. The epidermal growth factor protein (EGFR), cascade protein (ERK), and fibroblast growth factor proteins (FGFR and FGF) are involved in the different signaling pathways that lead to the formation of different products, that are responsible for the progression of cancer and thus can be considered as the therapeutic targets. Indigofera tinctoria, a medicinal plant with proven anti-cancerous properties, was chosen for this study to investigate its different compound’s therapeutic effects against the target proteins, which are responsible for prostate cancer. Methods: In this study, 20 different compounds were selected from the Indigofera tinctoria plant as ligands to check for their binding affinity against the target proteins (EGFR, ERK, FGFR, and FGF). The docking of the ligands with the target proteins was done by using the PyRx Virtual tool. The computational investigation of all the ligands and the target proteins, such as their molecular structure, phytochemistry, therapeutic actions, and other data was carried out. The protein structure validation and the pharmacological evaluation of the ligands were done using the BIOVIA Discovery Studio, pdb sum generate, and ADMET lab 2.0, respectively. Result: The results of this study showed that the compounds, Pseudosemiglabrin, [(12S,15R,16R)-14,14-dimethyl-6-oxo-4-phenyl-3,11,13-trioxatetracyclo [8.6.0.02,7.012,16] hexadeca-1(10),2(7),4,8-tetraen-15-yl] acetate, Deguelin, Sumatrol and Rotenone showed good binding affinity with the target proteins and can be considered as a potential drug for the prostate cancer. Conclusion: The compounds selected were found to be active against the target proteins for prostate cancer and thus can be utilized for cancer suppression. Further in vitro studies need to be done to support this study.
Keywords: ADMET lab 2.0; Indigofera tinctoria; Prostate cancer; epidermal growth factor receptors; extracellular regulated kinase; fibroblast growth factor receptors; molecular docking